2015
DOI: 10.1111/pan.12606
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of functional magnetic resonance imaging findings in children with and without a history of early exposure to general anesthesia

Abstract: Early anesthetic exposure and surgery did not affect accuracy, response time, or activation patterns in the primary region of interest during performance of the task. Intergroup differences in activation patterns in other areas of the brain were observed, and the significance of these findings is unknown. fMRI appears to be a useful tool in evaluating the long-term effects of early exposure to general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Brain development of rhesus macaques, corresponds closely to humans (neurodevelopment of rhesus monkeys at birth corresponds to that of a 6-month-old human 14,19 ), thus they are a highly relevant model for social functioning, complex behavior, and emotional state. So far, only three other studies have explored behavioral and/or cognitive outcomes after anesthesia exposure in young NHPs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Brain development of rhesus macaques, corresponds closely to humans (neurodevelopment of rhesus monkeys at birth corresponds to that of a 6-month-old human 14,19 ), thus they are a highly relevant model for social functioning, complex behavior, and emotional state. So far, only three other studies have explored behavioral and/or cognitive outcomes after anesthesia exposure in young NHPs.…”
Section: Introductionmentioning
confidence: 91%
“…12 It is less clear whether a single anesthetic exposure, particularly of short duration, is enough to trigger long-term sequelae in young children. While some retrospective studies identified an increased risk for developmental or behavioral disorder diagnosis even after a single short general anesthetic event, 13,14 other studies produced ambiguous results 15 or observed no increased risk. 16 In fact, one recent study suggests no risk at all, not even after multiple anesthetic exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the choices of drugs or treatment in children should be taken serious consideration. As shown by functional magnetic resonance imaging, general anesthetics used in children between 0 and 24 months of age would affect the development of cerebellum, cingulate gyrus, and paracentral lobule [16]. For examples, sevoflurane anesthesia reduces pro-social proteins oxytocin (OT) and arginine vasopressin (AVP) activities in the neonatal hippocampus and impairs social recognition memory formation and social discrimination ability in juvenile mice [17].…”
Section: Propofol Postnatal Administration Restricts Neurodevelopmentmentioning
confidence: 99%
“…While some retrospective studies identified an increased risk for developmental or behavioral disorder diagnosis even after a single short general anesthetic event, 13,14 other studies produced ambiguous results 15 or observed no increased risk. 16 In fact, one recent study suggests no risk at all, not even after multiple anesthetic exposures.…”
Section: Introductionmentioning
confidence: 99%